Data sharing statements for clinical trials: a cross-sectional survey of cardiology journals - Jingyi Zhang; Guowei Li; Yingxin Liu; Xinru Peng; Xuerui Bai; Zhixiong Cheng (BMJ Open)
Objective The International Committee of Medical Journal Editors requires data sharing statements in trial publications, but whether cardiology journals request data sharing statements in clinical trial submissions is unclear. We performed a survey to assess whether cardiology journals request data sharing statements in clinical trials.Design, setting, data source and participants All cardiac and cardiovascular systems journals that published clinical trials from January 2019 to December 2022 were included. The study outcome was journal requests for data sharing statements. Multivariable logistic regression analysis was used to examine the association between journal characteristics and journal requests. We also explored whether journal requests aligned with their subsequently published clinical trials.Results A total of 126 journals were included, among which 96 (76.2%) requested data sharing statements in clinical trials. Elsevier journals and Consolidated Standards of Reporting Trials endorsement had increased adjusted odds of requesting data sharing statements, with an OR of 5.74 (95% CI 1.45 to 22.70) and 7.21 (2.69 to 19.32), respectively. In the 78 journals that requested statements, 24 (30.8%) indeed did not publish any data sharing statement in their trial reports.Conclusions Approximately one in four cardiology journals did not request data sharing statements on clinical trial submissions, while a substantial inconsistency existed between journal requests and the actual publications of statements in their published trial reports.